WORK COMMITMENT AND WORK ADJUSTMENT AS CORRELATES OF PERFORMANCE EFFECTIVENESS OF GUIDANCE COUNSELLORS IN PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE - OKONKWO, MERCY CHIKA; EKWENZE, ANGELA UNOMA (Int’l Journal of Education Research and Scientific Development, 2024)
The study investigated work commitment and work adjustment as correlates of performance effectiveness of Guidance counsellors in public secondary schools in Anambra state. The main purpose of the study was to investigate the relationship between work adjustment, work commitment and counsellors’ performance effectiveness in public secondary schools in Anambra state. Four research questions and four null hypotheses guided. The study It was a correlational survey type. The population of the study comprised 226 respondents which include: principals, school counsellors and zonal education counsellors in all the six Educational Zones and 2 state counsellors. Due to the manageable size of the population, census sampling technique was used. A structured questionnaire developed by the researcher was used for data collection. Cronbach Alpha statistics was used in determining the reliability coefficients of the instrument and the overall reliability estimate was 0.81. Pearson Product Moment Correlation was used for analyzing the research questions while the hypotheses were tested using simple regression analysis. The result of the study showed among others that work commitment has a strong positive correlation with guidance counsellors’ performance effectiveness in public secondary schools in Anambra state and that work adjustment has a strong and negative correlation with guidance counsellors’ performance effectiveness in public secondary schools in Anambra state. Based on the findings, the study recommended among others that the government should establish a supportive work environment that fosters continuous professional development and recognition. This can include implementing mentorship programs, providing opportunities for skill building workshops and acknowledging counsellors’ contributions through rewards and recognition programs. This would go a long way to cultivate their sense of commitment and motivation which enhances their performance effectiveness.